Medieval and early modern devotional objects in global perspective: translations of the sacred - Robertson, Elizabeth; Jahner, Jennifer ca. 20./21. Jh. (The new middle ages, 2010)
"The fourteen essays create an interdisciplinary conversation about the nature and function of sacred and devotional objects across the globe during the medieval and Early Modern period. The discussion treats Buddhist, Morisco, Morrano, Christian, and South American Indian relics considered from the perspectives of experts in Buddhism, art history, literary analysis, history, philosophy, Spanish Studies, and Celtic Studies. The anthology reveals the surprising commonalty of the significance of sacred objects across the globe while at the same time delineating their varied functions. Among the shared issues considered in the collection are the nature of access to the object (who is allowed to see the object, how, and when), the way relics delineate sacred space, community formation via sacred objects (who is included and who is excluded in the sacred community), and appropriation and reappropriation of sacred and devotional objects (who controls what object, where, and when.)"--